Import competition and vertical integration: Evidence from India - Joel Stiebale; Dev Vencappa (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
Recent theoretical contributions provide conflicting predictions about the effects of product market competition on firms' organizational choices. This paper uses a rich firm-product-level panel data set of Indian manufacturing firms to analyze the relationship between import competition and vertical integration. Exploiting exogenous variation from changes in India's trade policy, we find that foreign competition, induced by falling output tariffs, increases backward vertical integration by domestic firms. The effects are concentrated in rather homogenous product categories, among firms that mainly operate on the domestic market, and in relatively large firms. Our results are robust towards different sub-samples and hold with or without conditioning on various firm- and product-level characteristics including input tariffs and firm-year fixed effects. We also provide evidence that vertical integration is associated with higher physical productivity, lower marginal costs and rising markups.
Keywords: F14; F61; L25; L22; L23; 330; Trade Liberalization; Competition; Vertical Integration; Innovation